Digital Amnesia: The Smart Phone and the Modern Indian Student - Swaminathan, Shakti (International Journal of Psychosocial Rehabilitation, 2020)
Digital Amnesia or the „Google Effect‟ is a new phenomenon. The „Google Effect‟ refers to the tendency to not remember information, when it can be looked up online. Drawing on this, the term „Digital Amnesia‟ was coined as part of Kaspersky, the cyber security firm‟s study, and refers to the “experience of forgetting information that you an trust an digital device to store and remember for you”. It suggests that in this age of the Internet, the reliance of technology has reached a point wherein gadgets are treated as an extension of the human brain. The presence of Internet and technology is changing the concept of memory. We choose to not remember pieces of information that is stored in our gadgets. While people may choose not to remember phone numbers or important dates, this paper also delves into the concept of memory erosion- if the reliance of technology erodes or tampers with existing memory, and the impact it has on the learning and retention abilities of students. The focus of the paper is primarily on two aspects- the prevalence of digital amnesia among students and its effect on learning. This is a trend paper that uses environmental scanning and future speculative analysis. Findings: The phenomenon is well established among the students and could be a cause for worry.